9.7k views
0 votes
Which rule represents the translation form the pre image ABC to the image A’B’C’

User Meadow
by
5.6k points

1 Answer

4 votes
The rest of the question is the attached figure.

As shown in the graph
The coordinates of the image ABC are:
A(-3,4) , B(-4,1) and C(-2,1)

And the coordinates of A'B'C' are:
A'(4,-2) , B'(3,-5) and C'(5,-5)

So,
A' - A = (4,-2) - (-3,4) = (7,-6) →(1)
B' - B = (3,-5) - (-4,1) = (7,-6) →(2)
C' - C = (5,-5) - (-2,1) = (7,-6) →(3)

So, from (1), (2) and (3)

The rule represents the translation form the pre image ABC to the image A’B’C’ is ⇒⇒⇒ (x, y) → (x + 7, y – 6)
Which rule represents the translation form the pre image ABC to the image A’B’C’-example-1
User Nishant Thapliyal
by
5.7k points